NORDIC MOBILITY COIN: En incitamentsmodel for grøn mobilitet - Christensen, Jakob Steen (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
Nordic Mobility Coin is a mobility platform with an incentive model that rewards users who walk, take the bike or share transportation. A holistic mobility concept that expands the concept of transport to cover the entire journey, whether is through shared mobility such as car-pooling or mass transport, biking and walking. The incentive platform will allow users to obtain a Nordic Mobility currency that can be used within different mobility sectors across Scandinavia. By gathering ‘mobility coins’ through walking, biking or taking the public transport, the user can use these coins to acquire rebates towards future transportation trips. For example, a person chooses to bike to the local train station, collect a cheaper train ride, and walk the remaining way to the office, and earn even more coins for the next trip. Or even better, a person bikes the entire journey and collects cheaper or even free tickets for use on public transport later. In suburban and rural areas with weaker coverage of public transport the platform will also reward shared cars, carpooling and even hitchhiking. The platform will use the concept of nudging and gamification, to be in line with how other commercial actors are building successful platforms. By allowing people to gather coins that can have financial value, we allow for the possibility of gamification that has proven to be successful when trying to achieve behavioral change. The impact of sustainable mobility reaches way beyond the scope of mobility. There have been numerous calculations of the societal cost connected to congestion, negative environmental impact, health, hazardous air quality, as well as the positive health benefits from walking and cycling etc. Ruter’s (Oslo- Akershus public transport) socio economic report suggests that for every 1 NOK that is invested in public transport (the report includes biking and walking together with public transport offerings) society receives 4.5 NOK in return. Therefore, it makes sense to create novel way of incentivizing and instantaneously rewarding citizens that contribute to society by choosing the most appropriate sustainable transport at any given time. With that in mind, the incentive system could go beyond public transport and include other brands and products that are supporting the underlaying vision of green mobility. One example could be a person who now walks to work might be able to collect enough coins to get a rebate on new sneakers, the gym or the cinema. For actors within the public sector, the incentives are a higher modal share of public transportation, with its positive environmental side effects, while for the commercial actors, this could be seen a corporate social responsibility project, where the rebates they offer create both commercial gains while they contribute towards a better future.